Delayed Response After Confirmed Progression (DR) and Other Unique Immunotherapy-Related Treatment Concepts in Cutaneous Squamous Cell Carcinoma - Lim, Annette M.; Cavanagh, Karda; Hicks, Rodney J.; McLean, Luke; Goh, Michelle S.; Webb, Angela; Rischin, Danny (Frontiers in Oncology, 2021)
Non-melanoma skin cancers are one of the most common cancers diagnosed worldwide, with the highest incidence in Australia and New Zealand. Systemic treatment of locally advanced and metastatic cutaneous squamous cell carcinomas has been revolutionized by immune checkpoint inhibition with PD-1 blockade. We highlight treatment issues distinct to the management of the disease including expansion of the traditional concept of pseudoprogression and describe delayed responses after immune-specific response criteria confirmed progressive disease with and without clinical deterioration. We term this phenomenon “delayed response after confirmed progression (DR)”. We also discuss the common development of second primary tumors, heterogeneous disease responses, and expanding clinical boundaries for immunotherapy use.